The Webs of Life: Review of The Sounds of Life (2022) and Gaia’s Web (2024) by Karen Bakker - De Bruyn, Ben (Humanimalia, 2025)
Review of:Karen Bakker, The Sounds of Life: How Digital Technology Is Bringing Us Closer to the Worlds of Animals and Plants. Princeton University Press, 2022. 368 pp. $33.00 (hb).andKaren Bakker, Gaia’s Web: How Digital Environmentalism Can Combat Climate Change, Restore Biodiversity, Cultivate Empathy, and Regenerate the Earth. MIT Press, 2024. 288 pp. $29.95 (hb)